If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 130 = x + 137 Reorder the terms: 130 = 137 + x Solving 130 = 137 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 130 + -1x = 137 + x + -1x Combine like terms: x + -1x = 0 130 + -1x = 137 + 0 130 + -1x = 137 Add '-130' to each side of the equation. 130 + -130 + -1x = 137 + -130 Combine like terms: 130 + -130 = 0 0 + -1x = 137 + -130 -1x = 137 + -130 Combine like terms: 137 + -130 = 7 -1x = 7 Divide each side by '-1'. x = -7 Simplifying x = -7
| 5(-3.4k+-7)+(3k+21)= | | X+127=x+67 | | 1.25+.25x=8.00 | | X+27=x+67 | | 94/1000 | | -3k+5k-4+4k= | | 15x=11x-2 | | 116=18x+8 | | 16=3x+5x | | 1x-2-2.1(x+2)=3(x+1.5) | | 9s=62 | | -7(y+1)+2y=8 | | f-66=242 | | 22y=33y | | 723144=0 | | M-3-2m=-3 | | 1+3r-2r=3 | | z=5x+6b-3x-2x | | 1.7a+0.3a=45 | | -19+x=20-42+10 | | 15-3z=-4.5 | | (M+2)x+(m^2-1)y+m^2+M+1=0 | | (p^3/2)^-2 | | 3x-(7x+5)=8x+2(x-3) | | 2x+21+4x+15=x | | 2(-3x+4)-3(3-3x)=44 | | 11a*2+a+6a*3+9a*2+9= | | f(x)=x-2x-2 | | 65.95+12=275.80 | | 17+p=3(13-p) | | X(35-2x)+X(35-2x)+(70-2x)(x)+(70-2x)(x)= | | 21=-7/9y |